Modeling of soil quality in Umonyeche Milieu Southern Region of Nigeria using Heavy Metal Index and Spatial Distribution (British Journal of Multidisciplinary and Advanced Studies, 2026)
This study examined the presence of heavy metals (HMs) in soil samples collected from Umuonyeche in Owerri, Imo State, southeastern Nigeria. Metal concentrations were determined using Atomic Absorption Spectroscopy. To assess pollution levels, multiple indices were applied, including the Potential Ecological Risk Index (ERI), Geo-accumulation Index (Igeo), Contamination Degree (Cdeg), and Nemerow Pollution Index (PNI). Statistical tools such as the Pearson correlation matrix and Principal Component Analysis (PCA) were also used to evaluate the relationships among metals and identify their possible sources. The results showed that heavy metal contamination in the study area largely originates from anthropogenic activities, including automobile repairs, solid waste disposal, and agricultural practices. While the ERI suggested that the soil is mostly unpolluted, the Igeo results indicated the influence of human activities, highlighting a contrast between the two indices. The Cdeg values revealed a low level of contamination across the samples. Additionally, PNI assessments categorized the soils as 25.8% clean, 28.2% slightly clean, and 10.7% moderately polluted. Findings from PCA and the Pearson correlation matrix further confirmed that the heavy metals present in the soil are primarily linked to human activities.